Risk Difference of Stroke Based on Biological Risk Factor for Working Age Group - Eka Oktaviani Rahayu (Universitas Airlangga, 2016)
Indonesia is a country with the highest stroke mortality in Southeast Asia. An increase in cases of stroke in the productive age-related to unhealthy lifestyles in Indonesia. This study aims to analyze differences in stroke risk based on biological risk factors at a productive age. The study used a case-control design with a sample size of 33 people in the case group and 33 people in the control group, the sample was selected using systematic random sampling techniques. This research was conducted at the Haji Public Hospital Surabaya in October-May 2015. The dependent variable is the incidence of stroke, while the independent variables are age, hypertension, diabetes mellitus (DM) type 2, hypercholesterolemia, and coronary heart disease. Data are presented descriptively and analyzed bivariate and multivariate with Odds Ratio (OR), Risk Difference (RD), and logistic regression. The results showed that history of hypertension (OR = 45; 95% CI = 8.75-274.4; RD = 0.73), type 2 DM (OR = 5.71; 95% CI = 1.26-29 , 39; RD = 0.39), hypercholesterolemia (OR = 18.6; 95% CI = 3.41–133.91; RD = 0.57), and coronary heart disease (OR = 13.91; 95% CI = 1.61-311.02; RD = 0.49) affect the incidence of stroke in the productive age group. It was concluded that in the productive age group, hypertension, type 2 diabetes, hypercholesterolemia, and coronary heart disease can increase the risk of stroke. Education about stroke needs to be done especially about the prevention of hypertension, type 2 diabetes, hypercholesterolemia, coronary heart disease, and monitoring patients at risk of stroke with regular health checks to prevent strokes at productive age.